Prevalence of Dental Anomalies in Various Categories of Malocclusion among Orthodontic Patients in the Kosovo Region: A Retrospective Study - Selmani, Mimoza; Bukleta, Manushaqe Selmani (European Journal of General Dentistry, 2023)
Objectives The objective of this retrospective research was to investigate the prevalence and the association between dental anomalies and malocclusion in a subset of Kosovo's population.Materials and Methods This retrospective descriptive study was conducted by recruiting 557 patients; 215 (38.6%) were males and 342 (61.4%) were females. The age range was from 7 to 44 years. The exclusion criteria were employed for the sample size, and 307 of 864 patients were excluded from the study. Malocclusion groups were divided through Angle's classification, and dental anomalies were defined according to the literature. Pretreatment panoramic radiographs, medical and dental history, study casts, and photographs were included to categorize malocclusion and identify dental anomalies (i.e., hypodontia, ectopic eruption, impaction, and diastema). The data were analyzed with IBM SPSS software version 16.0. The chi-squared test was utilized to calculate the frequency and percentages of malocclusion and dental anomalies. A p-value of 0.05 was considered statistically significant.Results Five hundred and fifty-seven patient records from 2015 to 2020 were included. An increased prevalence of ectopic eruption (24.8%) was found in this study, whereas the least common was hypodontia (7.0%). The most common malocclusion was class I (46.9%). Vertical plane malocclusion demonstrated that 31.4% had a deep bite and 9.5% had an open bite. Most dental anomalies were significantly associated with class I malocclusion and least associated with class III malocclusion. Transverse malocclusion exhibited that 14% had anterior crossbite and 10.8% had posterior crossbite. Posterior crossbite was significantly less in the class III malocclusion group (p = 0.019).Conclusion The prevalence of the selected dental anomalies was overall high in our study; 557 of 864 patients faced dental anomalies. An association was seen between malocclusion and dental anomalies in the Kosovan population, especially with class I malocclusion. Deep bite was prominent in the vertical plane malocclusion, whereas anterior crossbite was the most common finding in the transverse plane. Anterior crowding was prevalent in the maxilla and posterior crowding in the mandible.
Keywords: malocclusion; prevalence; dental anomalies; orthodontics